Peningkatan Daya Saing Produk Hasil Laut Melalui Strategi Usaha, Inovasi Olahan, Dan Digital Marketing Pada Masyarakat Desa Lontar: Enhancing the Competitiveness of Marine Products Through Business Strategies, Processed Product Innovation, and Digital Marketing in the Lontar Village Community - Melia Handayani; Wafa Nurul Hakim; Syifa Fajar Maulani; Siti Kurotul Ainiah; Wenny Ananda Larasati; Faishal Sauqi Rammadhani (Indonesia Berdaya, 2026)
Abstract. This community service activity was carried out in Lontar Village, Tirtayasa District, Serang Regency, Banten, which is known as a coastal area with main potential in the fisheries and seaweed cultivation sectors. The problems faced by the local community include limited knowledge of modern packaging innovations, business consistency strategies, and digital-based marketing, resulting in marine products that have not yet reached optimal added value. The method consisted of four stages: field surveys, interviews, planning, and implementation. The implementation series included a pre-test, delivery of material, workshops, and a post-test. The materials presented covered entrepreneurship strategies, packaging innovation using tools such as vacuum sealers, and digital marketing training through the creation of online stores on e-commerce platforms. The results showed an increase in participants’ knowledge and skills, with an average improvement of 14% from pre-test to post-test. The largest increase was in digital marketing at 26.12%, followed by modern packaging innovation at 13.04%, and entrepreneurship strategies at 6.95%. This demonstrates that the training successfully increased motivation, practical skills, and the community’s readiness to develop their businesses. Through this assistance, the Lontar Village community not only learned theory but also directly practiced digitalization skills, modern packaging, and online marketing to expand their markets. This activity is expected to encourage increased added value of marine products, strengthen competitiveness, and support the sustainable economic independence of coastal communities. Abstrak. Kegiatan pengabdian kepada masyarakat ini dilaksanakan di Desa Lontar, Kecamatan Tirtayasa, Kabupaten Serang, Banten, yang dikenal sebagai wilayah pesisir dengan potensi utama pada sektor perikanan dan budidaya rumput laut. Permasalahan yang dihadapi masyarakat setempat meliputi keterbatasan pengetahuan dalam inovasi pengemasan modern, strategi konsistensi usaha, dan pemasaran berbasis digital, sehingga hasil laut yang diproduksi belum memiliki nilai tambah optimal. Metode kegiatan dilakukan melalui empat tahapan, yaitu survei lapangan, wawancara, perencanaan, dan pelaksanaan. Rangkaian pelaksanaan mencakup pre-test, pemberian materi, workshop, serta post-test. Materi yang disampaikan meliputi strategi kewirausahaan, inovasi pengemasan menggunakan alat seperti vacuum sealer, dan pelatihan pemasaran digital melalui pembuatan toko online di platform e-commerce. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan peserta dengan rata-rata kenaikan sebesar 14% dari pre-test ke post-test. Peningkatan terbesar terjadi pada aspek pemasaran digital sebesar 26,12%, diikuti oleh inovasi pengemasan modern sebesar 13,04%, serta strategi berwirausaha sebesar 6,95%. Hal ini membuktikan bahwa pelatihan mampu meningkatkan motivasi, keterampilan praktis, dan kesiapan masyarakat dalam mengembangkan usaha. Dengan adanya pendampingan ini, masyarakat Desa Lontar tidak hanya belajar teori, tetapi juga bisa langsung mempraktikkan keterampilan digitalisasi, pengemasan modern, dan pemasaran online untuk memperluas pasar. Kegiatan ini diharapkan dapat mendorong peningkatan nilai tambah produk hasil laut, memperkuat daya saing, serta mendukung kemandirian ekonomi masyarakat pesisir secara berkelanjutan.